What is worth a qualification? : Approaches towards the recognition of vocational qualifications and competences acquired abroad - Eberhardt, Christiane [Verfasser]; Annen, Silvia [Verfasser] (My University, 2014)
"In Germany the recognition of foreign qualifications and competences is of high political relevance due to the severe problem of a skills shortage. Thus, in April 2012 the 'Federal Recognition Act' entered into force in order to improve the assessment and recognition of vocational qualifications achieved abroad. The presented research project MoVA reflects the implementation of this act by analyzing the strategies, concepts and practices of other countries regarding recognition of vocational competences and qualifications. In this contribution we focus on the present status in Germany and counter it with the approaches implemented in Denmark, Canada and Australia." (Authors' abstract, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; I 2.3.5 Australien, Ozeanien; Anrechnung von Bildungsleistungen; Anerkennungsgesetz; Implementation; Internationaler Vergleich; Bundesrepublik Deutschland; Dänemark; Kanada; Australien